Aligning International Collaborative Research to Global and National Objectives: An Analysis of Research Objectives in Uganda Using Text Analysis and Natural Language Processing - S, Sebbale,; A, Byamugisha, (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Like many developing countries, Uganda’s engagement in international research collaboration has been on the increase. Evidence from this and other types of research is intended to shape policy and development outcomes for sustainable development. Uganda’s development roadmap is reflected in its National Vision 2040 with its constituent five-year National Development Plans. These Plans are designed and aligned to other global development roadmaps, like the Sustainable Development Goals. Unfortunately, no research has been to track the alignment of IRC to these national and global development objectives. As a result, research is undertaken within a structural vacuum and the evidence it generates hardly influences policy. This research paper investigates the alignment of research projects conducted in Uganda between 2015 and 2020 with Sustainable Development Goals (SDGs), The National Development Plan III objectives, and NRM government Manifesto programs. By analyzing a comprehensive collection of research projects, the study aims to uncover hidden patterns, relationships, and insights, ultimately shedding light on research trends and providing guidance to policymakers and the research community. Several researchers have explored the alignment between research activities and specific Sustainable Development Goals (SDGs), highlighting the need for targeted efforts to address specific challenges (Smith et al., 2018; Johnson & Brown, 2020). Text mining techniques have emerged as a promising solution for analysing research literature, including identifying trends and assessing relevance to specific goals (Li et al., 2017; Chen et al., 2019). The objective of this study is to map the existing research registered in Uganda onto the NDPIII, Vision 2040 and Sustainable Development Goal Objectives to generate new evidence on the future alignment of research objectives to national development objectives. The methodology involved data acquisition and preprocessing, descriptive statistical analysis, qualitative analysis using text mining techniques, and natural language processing (NLP). The data was cleaned and analyzed using Excel and R programming. Descriptive analysis provided an overview of research distribution, while text mining identified key themes and connections between research titles and objectives. NLP was used to score and classify projects based on titles and objectives by leveraging the Ada Davinci Large Language OpenAI model. The combination of NLP and R programming allowed for efficient analysis of the data. Analysis indicates a significant surge in registered research projects in 2017, showcasing remarkable growth, collaboration, and dedication within the scientific community. Most projects (80.37%) were collaborative, indicating a culture of international cooperation. The text mining analysis of research objectives reveals key focus areas and central concepts such as Uganda, HIV, health, care, and women. The analysis also shows a shift in key words and focus areas over time, with a reduction in research on HIV and an increased focus on Uganda. The text mining analysis of research titles aligns with the findings from the objectives, highlighting the prominence of Uganda, HIV, health, study, and evaluation. Overall, there is consistency in the focus areas before and after 2019, with a potential shift towards gender-related research and more specific study areas within Uganda. the paper also analyzed the alignment of international collaborative research with global and national objectives. The findings revealed that research projects primarily focused on Clean Water and Sanitation and Good Health and Well-being (19.4% and 18.0% respectively), while Affordable and Clean Energy and Decent Work and Economic Growth had limited representation (0.6% each). Regional Development and Tourism Development showed high alignment with NDP III objectives (27.6% and 25.6% respectively), while Governance and Security, Manufacturing, and Sustainable Urbanization and Housing had lower alignment. Collaborative research made significant contributions to delivering education and health (52.4%), ensuring justice and equity (23.5%), and protecting life and property (10.8%) in the NRM Manifesto programs. The results suggest the importance of collaborations, interdisciplinary research, and resource allocation for achieving sustainable development goals.